2010
DOI: 10.1007/s10897-010-9299-8
|View full text |Cite
|
Sign up to set email alerts
|

“The Cancer Bond”: Exploring the Formation of Cancer Risk Perception in Families with Lynch Syndrome

Abstract: This study explores the social context of hereditary cancer risk perception in three families, an African-American family, a Mexican-American family, and a Caucasian family, each with Lynch Syndrome documented by a mismatch repair gene mutation. Communication network assessments measured family communication about cancer experiences and genetic testing information among a total of 26 participants. Participant narratives were evaluated to gain insight into how family cancer experiences and genetic testing infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 26 publications
(38 reference statements)
3
27
0
1
Order By: Relevance
“…Only 4% of participants were non-carriers, 30% were former cancer patients, and 66% were mutation carriers. In the light of these results, one might hypothesise that families perceived the family interview as directed to those who were primarily linked by the illness or at-risk status, under the gaze of the ''cancer bond'' [10]. On average, each interviewed family represented 3 households (27/9), including 2-3 generations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only 4% of participants were non-carriers, 30% were former cancer patients, and 66% were mutation carriers. In the light of these results, one might hypothesise that families perceived the family interview as directed to those who were primarily linked by the illness or at-risk status, under the gaze of the ''cancer bond'' [10]. On average, each interviewed family represented 3 households (27/9), including 2-3 generations.…”
Section: Discussionmentioning
confidence: 99%
“…Family history and formation of risk awareness Findings elucidate the pivotal role of the cumulative effect of cancer-related events (diagnosis of cancer, cancer recurrence, and deaths) in giving rise to increased concern about cancer risk [10]. Each person starts by comparing the history of cancer-affected relatives with their own history and the history of their children; for instance, reaching the age of the affected mothers seemed to add a supplementary feeling of vulnerability to HBOC [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…44,45 The risks and benefits both of revealing and of withholding a clinical or molecular diagnosis of cancer predisposition have been the subject of extensive debate in the literature. [46][47][48] Psychological harm may be involved in issues such as increased worry about cancer risk, the need for periodic laboratory and imaging tests and the anxiety that precedes and follows them, and the burden of testing itself. Some studies have found that a passive, pessimistic coping style, low social aspirations, and precarious social support networks also have a negative impact on mutation carriers, as does negative perception of the disease and the risk of cancer itself.…”
Section: Psychological Aspectsmentioning
confidence: 99%
“…: [42, 44, 49, 60, 68, 70, 87, 89, 106, 107, 116, 135, 140, 141] b Refs: [86, 94, 130] c Refs: [23, 24, 2830, 45, 51, 71, 72, 7678, 98, 103, 109111, 117, 127129, 131, 132, 138, 139, 142, 146, 147, 153] d Refs: [33, 34, 36, 40, 57, 67, 69, 83, 95, 97, 102, 118, 122, 148, 149, 152] e Refs: [55, 85, 105, 126, 130] f Refs: [43, 46, 52, 66, 73, 74, 79, 80, 88, 90, 92, 99101, 104, 108, 114, 136, 143, 154] g Refs: [27, 31, 35, 38, 39, 41, …”
Section: Figmentioning
confidence: 99%